Արցախի ժամանակակից խաչքարային մշակույթը - Սաֆարյան, Անուշ (Հայաստանի պատմության թանգարան)
Khachkar, undergoing ideological, iconographic, thematic and substantive changes during its centuries-long existence, continues to be one of the most important symbols of Armenian national identity.In the 60s of the last century, when the new stage of khachkar-making began in Armenia, it did not gain much popularity in Artsakh, center of Azerbaijan's culture-destroying policy. In fact, if in different regions of Armenia we can talk about khachkars as a serious cultural phenomenon, then in Artsakh we are able to talk about its separate, individual manifestations. Only after the first Artsakh war, the khachkar became the main symbol of marking and sanctifying the liberated territories, settlements and especially the borders, including corresponding dimensional and iconographic changes. This report discusses the developments and transformations of the Artsakh khachkar culture, the features of khachkar construction, the process of "khachkarization" of the territories liberated as a result of the first Artsakh war. Хачкары, претерпевшие символические, изобразительные, тематические и содержательные изменения, были и остаются важными символами армянской конфессиональной и национальной идентичности. В 60-х годах прошлого века, когда в Армении начался новый этап хачкаростроения, хачкарное дело не получило большой популярности в Арцахе, находившемся в центре культуроразрушающей политики Азербайджана. По сути, если в разных регионах Армении можно говорить о хачкарах как о серьезном культурном явлении, то в Арцахе можно говорить об отдельных его проявлениях. Только после первой Арцахской войны хачкар стал главным символом обозначения и освящения освобожденных территорий, населенных пунктов и особенно границ, включая соответствующие объемные и иконографические изменения. В докладе рассматриваются развитие и трансформации арцахской хачкарной культуры, особенности хачкаракостроения, процесс хачкаризации территорий, освобожденных в результате первой Арцахской войны.
Keywords: Մշակութային մարդաբանություն